Pengaruh Fraksi Volume Serat dan Lama Perendaman Alkali terhadap Kekuatan Impak Komposit Serat Aren-Polyester - M. Budi Nur Rahman , Bambang Riyanta , Kuncoro Diharjo (Semesta Teknika, 2011)
Palm fiber waste in the industrial processing of starch sugar palm has potential as reinforcing material composite material. This research to determine the effect of fiber volume fraction and long immersion in alkaline solution (NaOH) 5% for the impact strength composites waste palm fiber-polyester. The material used is a waste of palm fiber, unsaturated polyester 157 BQTN, MEKPO catalyst and 5% alkaline solution. Preparation of composites made by the method of press mould. The Composites made with variations of the volume fraction of 10%, 20%, 30%, 40%, 50% and long immersion alkali solution is 0, 2, 4, 6, and 8 hours. The impact test conducted by Izod impact testing machine refers to the standard ASTM D 5941. The results showed that increasing the volume fraction will increase the impact strength, but the subsequent decline. The longer the alkali treatment will reduce the impact strength because the fiber has undergone treatment. The impact strength maximum of the composites with fiber volume fraction of 40% and without alkaline immersion of 0.3211 J/mm2. Characteristics of a broken section of palm fiber composite material are a polyester matrix of a single fracture.